Penerapan Model Pembelajaran SSCS (Search, Solve, Create, Share) untuk Meningkatkan Hasil Belajar IPA Siswa Kelas V SD - Satriani Satriani; Muhammad Irfan; muhammad amran; Andi Muspidayanti (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
This research is a classroom action research that aims to find out how the application of the SSCS (Search, Solve, Create, Share) learning model to improve students' science learning outcomes. The formulation of the problem in this study is whether the application of the SSCS learning model can improve science learning outcomes for fifth grade students of SD Negeri 1 Kodeoha, North Kolaka Regency. The data collection instrument used documentation, tests and observations. Data analysis techniques in this study are data reduction, data modeling and drawing conclusions. Based on the results of the research in the first cycle the teacher did not provide guidance to students so that students did not dare to express their opinions, while in the second cycle students had the courage to express their opinions with the help and guidance of the teacher which indicated the existence of a teaching and learning process that resulted in changes as learning outcomes that showed learning objectives. achieved thus, the application of the SSC learning model can improve students' science learning outcomes.